Statement by Mr. R.ALTANGEREL, State Secretary for Foreign Affairs of Mongolia in the General Debate of the 59th Session of the United Nations General Assembly - Altangerel, R (Mongolian Journal of International Affairs, 2013)
DOI: http://dx.doi.org/10.5564/mjia.v0i12.98 Mongolian Journal of International Affairs No.12 2005: 96-103